Characterisation of Sputter Deposited of Thin Film Strain Sensors for Wearable Technology - Yulcifly, Nur Ashikin Zulaikha; Ali, Ahmad Hadi (Enhanced Knowledge in Sciences and Technology, 2025)
The increasing demand from industries in wearable technologies required a flexible and high sensitivity thin films. The study investigates the characterization and deposition of gold thin films on glass and polyethylene terephthalate (PET) samples as substrate for wearable technology applications. Sputtering method was applied to achieve uniform and high quality thin films, meanwhile four point probe, temperature testing, and flexibility testing used to determine electrical resistivity, thermal stability and mechanical performance. PET shows superior conductivity compared to glass and exhibited better flexibility under stress conditions. Temperature testing shows a linear resistance increase with rising temperatures, claimed thermal sensitivity. As result highlight the suitability of PET for flexible electronics due to its lower resistivity, mechanical stability, adaptability when stress applied, providing views for advancing thin film technology in wearable applications.